Flower girls - Cameron, Richard (Methuen Drama, 2007)
'Flower Girls' is the funny, beautifully observed and uplifting story of a group of disabled women who live and work at The Crippleage, Edgware. Inspired by the personal testimony and reminiscences of real-life Flower Girls, the play shifts effortlessly between the unsettled early years of World War II and the seemingly more liberated world of 1965. Their stories reveal an indomitable spirit and a fierce determination to find their place in the world, a world that prefers to keep them at a safe distance. 'Flower Girls' was commissioned by the Graeae Theatre Company and John Grooms and first toured as a co-production between Graeae and the New Wolsey Theatre Ipswich in October 2007.
10.5040/9781408191095.00000003
Keywords: Drama; Women with disabilities; Group homes for people with disabilities